Pemetaan Keberadaan Tempat Pengolahan Sampah 3R (Reuse, Reduce, Recycle) dalam Upaya Mewujudkan Zero Waste di Kabupaten Tangerang - Nabeela Qurratu’aini; Budi Hartono (Universitas Malahayati Lampung, 2025)
ABSTRACT The waste problem in Tangerang Regency is becoming increasingly complex due to its rapid population growth. The local government has established 3R (Reduce, Reuse, Recycle) Waste Processing Sites to help reach the zero-waste goal, but making these efforts truly effective remains a challenge. This study aims to map the locations of the 3R Waste Processing Sites (TPS), assess their operational effectiveness, and identify the primary challenges in waste management. We used spatial analysis with the Quantum Geographic Information System (QGIS) version 3.34 LTR to do this. All 29 3R TPS in Tangerang Regency were included, serving as both the population and the sample for our research. We relied on secondary data from relevant agencies. The results show that while there are 29 3R TPS, only 14 are actively operating. The main challenges include uneven service coverage, low waste absorption capacity, and a limited number of 3R TPS, particularly in densely populated areas, which generate high amounts of waste. To better address these issues, the Tangerang Regency Government should focus on increasing the number of 3R TPS and distributing them more evenly, with a particular emphasis on densely populated areas with high waste production. Additionally, encouraging active community participation in waste management through the 3R TPS is crucial to the program's success. Keywords: GIS, Waste Management, TPS 3R, Zero Waste ABSTRAK Permasalahan persampahan di Kabupaten Tangerang semakin kompleks seiring pertumbuhan jumlah penduduk yang tinggi. Pemerintah telah mengembangkan Tempat Pengolahan Sampah 3R (Reduce, Reuse, Recycle) untuk mendukung target zero waste, namun efektivitasnya masih menjadi tantangan. Penelitian ini bertujuan untuk memetakan distribusi TPS 3R, mengevaluasi efektivitasnya, serta mengidentifikasi hambatan utama dalam pengelolaan sampah. Metode yang digunakan adalah analisis spasial dengan aplikasi Quantum Geographic Information System (QGIS) versi 3.34 LTR. Hasil penelitian menunjukkan terdapat 29 TPS 3R di Kabupaten Tangerang, tetapi hanya 14 yang aktif beroperasi. Jangkauan layanan yang belum merata, kapasitas daya serap sampah yang rendah, dan keterbatasan jumlah TPS 3R menjadi kendala utama, terlebih dengan tingginya jumlah timbulan sampah akibat kepadatan penduduk. Oleh karena itu, diperlukan strategi penguatan, mulai dari penambahan jumlah dan pemerataan distribusi TPS 3R, peningkatan kapasitas pengelolaan, hingga keterlibatan aktif masyarakat untuk mencapai pengelolaan sampah yang lebih efektif. Kata Kunci: GIS, Persampahan, TPS 3R, Zero Waste